THE RHETORIC OF DISCOURSE AND PRAGMATICS IN LANGUAGE ANALYSIS (The Journal of Interdisciplinary Human Studies, 2026)
This study aims to explore the contributions of pragmatics to thedevelopment of discourse-analysis mechanisms by examining the interaction betweenlinguistic structure and pragmatic context in the production of meaning. The research isbased on the assumption that discourse comprehension cannot be achieved solely throughlinguistic elements; rather, it requires consideration of the communicative circumstancesand contextual factors related to both the speaker and the listener. The analytical methodwas employed to examine a set of discourses, with a focus on key pragmatic concepts suchas intentionality, implicature, and presupposition. The findings reveal that pragmaticsprovides precise tools for discourse analysis and for understanding its communicative andpersuasive dimensions, making it one of the fundamental approaches in contemporarylinguistic studies.
Keywords: pragmatics, discourse, context, intentionality, communication